In vivo oxidative stress in brain of Alzheimer disease transgenic mice: Requirement for methionine 35 in amyloid β-peptide of APP - Butterfield, D. Allan; Galvan, Veronica; Lange, Miranda Bader; Tang, Huidong; Sowell, Renã A.; Spilman, Patricia; Fombonne, Joanna; Gorostiza, Olivia; Zhang, Junli; Sultana, Rukhsana; Bredesen, Dale E. (Free radical biology & medicine, 2010)
Numerous studies have demonstrated oxidative damage in the central nervous system in subjects with Alzheimer disease and in animal models of this dementing disorder. In this study, we show that transgenic mice modeling Alzheimer disease—PDAPP mice with Swedish and Indiana mutations in the human amyloid precursor protein (APP)—develop oxidative damage in brain, including elevated levels of protein oxidation (indexed by protein carbonyls and 3-nitrotyrosine) and lipid peroxidation (indexed by protein-bound 4-hydroxy-2-nonenal). This oxidative damage requires the presence of a single methionine residue at position 35 of the amyloid β-peptide (Aβ), because all indices of oxidative damage in brain were completely prevented in genetically and age-matched PDAPP mice with an M631L mutation in APP. No significant differences in the levels of APP, Aβ(1–42), and Aβ(1–40) or in the ratio Aβ(1–42)/Aβ(1–40) were found, suggesting that the loss of oxidative stress in vivo in the brain of PDAPP(M631L) mice results solely from the mutation of the Met35 residue to Leu in the Aβ peptide. However, a marked reduction in Aβ-immunoreactive plaques was observed in the M631L mice, which instead displayed small punctate areas of nonplaque immunoreactivity and a microglial response. In contrast to the requirement for Met at residue 35 of the Aβ sequence (M631 of APP) for oxidative damage, indices of spatial learning and memory were not significantly improved by the M631L substitution. Furthermore, a genetically matched line with a different mutation—PDAPP(D664A)—showed the reverse: no reduction in oxidative damage but marked improvement in memory. This is the first in vivo study to demonstrate the requirement for Aβ residue Met35 for oxidative stress in the brain of a mammalian model of Alzheimer disease. However, in this specific transgenic mouse model of AD, oxidative stress is neither required nor sufficient for memory abnormalities.